Striving to establish patient participation in rehabilitation: the challenges experienced by nursing staff when changing practice to include the patient's perspective - Steensgaard, Randi; Kolbaek, Raymond; Kasch, Helge; Angel, Sanne (Frontiers in Rehabilitation Sciences, 2024)
PurposePatient participation is a complex issue and difficult to establish, but essential to successful spinal cord injury rehabilitation. The purpose of this study was to explore the challenges experienced by nursing staff when they wanted to include the patient's perspective in their rehabilitation.MethodsAction research methodology was applied to increase knowledge, develop competences, and ultimately change practice. Over a period of two years, four nurses and four certified healthcare workers participated in identifying, testing and evaluating ways to improve patient participation. The data consist of evaluations of patient participation and recorded and transcribed dialogues from meetings and workshops. Transformed into text, data were analysed using the interpretive theory of Ricoeur to identify central themes.FindingsThree central themes highlight the challenges experienced by the nursing staff while focusing more on patient participation in nursing practice: (1) Struggling to really listen to the patient's perspective, (2) Searching for time to listen to the patient's perspective, (3) Legitimising the patient's perspective in rehabilitation.ConclusionEven though nursing staff found patient participation to be vital for individualised rehabilitation, it was difficult to include the patient's perspective. The inclusion was challenged on a personal level, within the nursing group, and in the organisation due to prioritizing physical nursing tasks over the patient's perspective. Thus, the nursing staff struggled to change their nursing practice and to convince their colleagues and leaders that the rehabilitation should be re-organised to perform their nursing role to the full. This indicated a need to work on the attitude and approach of the entire organisation to promoting patient participation and nursing rehabilitation.